Development and piloting of a mother and child intervention to promote resilience in young children of HIV-infected mothers in South Africa. - Visser, Maretha; Finestone, Michelle; Sikkema, Kathleen; Boeving-Allen, Alex; Ferreira, Ronel; Eloff, Irma; Forsyth, Brian (Evaluation and program planning, 2012)
This paper describes the process of developing a parallel intervention for HIV-positive mothers and their young children (6-10 years) with a view to strengthening the relationship between them. Strong mother-child relationships can contribute to enhanced psychological resilience in children. The intervention was developed through action research, involving a situation analysis based on focus group discussions; intervention planning, piloting the intervention and a formative evaluation of the intervention. Participants supplied feedback regarding the value of the intervention in mother-child relationships. The findings obtained from the formative evaluation were used to refine the intervention. Two parallel programmes for mothers and children (15 sessions each) were followed by 10 joint sessions. The intervention for mothers focused on maternal mental health and the strengthening of their capacity to protect and care for their young children. The intervention for children addressed the development of their self-esteem, interpersonal relationships and survival skills. The formative evaluation provided evidence of good participation, support and group cohesion. Qualitative feedback indicated that the activities stimulated mother-child interaction. A similar intervention can easily be applied elsewhere using the detailed manual. The insights gained and lessons learnt related to mother and child interaction within an HIV-context that emerged from this research, can be valuable in other settings, both in Sub-Saharan Africa and elsewhere.
Keywords: Adaptation, Psychological; Adult; Child; Early Intervention (Education); Female; HIV Infections; Humans; Male; Maternal Welfare; Mental Health; Mother-Child Relations; Mothers; Pilot Projects; Program Development; Self Concept; Social Support; South Africa; Young Adult